2015
DOI: 10.1111/codi.12958
|View full text |Cite
|
Sign up to set email alerts
|

Impact of smoking on the surgical outcome of Crohn's disease: a propensity‐score matched National Surgical Quality Improvement Program analysis

Abstract: In patients with CD, the detrimental effects of smoking on surgical outcomes are driven by infectious and pulmonary complications, and by an increased likelihood of readmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 30 publications
0
8
1
Order By: Relevance
“…Smoking is known to complicate both the surgical and the medical management of CD, and to increase both the rate and the severity of infectious complications following colorectal surgery. [20][21][22] Work by Midura et al showed smoking status to be an independent predictor of anastomotic leak.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is known to complicate both the surgical and the medical management of CD, and to increase both the rate and the severity of infectious complications following colorectal surgery. [20][21][22] Work by Midura et al showed smoking status to be an independent predictor of anastomotic leak.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies examining readmission risk in IBD have either been single-center studies or have focused on surgical patients [ 10 , 11 ]. As such, understanding risk factors such as patient specific comorbidities, socioeconomic factors and hospitalization factors leading to readmissions among a large IBD cohort could allow for guided quality improvement interventions aimed at decreasing readmission rates.…”
Section: Introductionmentioning
confidence: 99%
“…We have performed MVA with subgroup analyses which demonstrate similar trends. However, some variables have not been adjusted for and need to be considered when interpreting our results: smoking status, which is known to be associated with postoperative morbidity, 40 was not included in the analysis due to inconsistent reporting; we also did not collect data regarding comorbidities or operating time which have been associated with worse outcomes 4,41 . Nevertheless, the median age in the ITT and non‐optimised cohorts was <45 years where the likelihood of multimorbidity is low 42 .…”
Section: Discussionmentioning
confidence: 99%